Sustainability balanced scorecard architecture and environmental investment decision making: The mediating and moderating effects of knowledge and risk indicators / Suaad Jassem - Suaad , Jassem (2020)
According to a survey by Bain and Company, the majority of the sustainability programs undertaken by global companies fail to meet their objectives. A part of the reason for such a dilemma is possibly due to the dearth of sufficient research on how investment and performance evaluation tools such as sustainability balanced scorecards architecture impact decisions taken by managerial decision-makers. Hence, this doctoral research endeavor extends the literature on sustainability balanced scorecards (SBSC) architecture by examining how they influence decision-makers when they attempt to achieve environmental goals of their organization through evaluation of environmental investment options. An experimental research model is proposed in this study developed by leveraging the premise of the Adaptive Decision Maker Framework and also the loss aversion component of the Prospect Theory. The goal of the study is to determine if significant difference exists between SBSC with sustainability parameters embedded with the four BSC perspectives (referred to as SBSC-4) and SBSC with sustainability as an additional fifth perspective (referred to as SBSC-5), when decision-makers use them to make environmental investment decision-making. The study also investigates the role of SBSC knowledge as a possible mediator and risk indicators as a possible moderator in the above relationships. The experiment was conducted on 108 managers working in multinational manufacturing companies, where the participants were selected from two different geographical regions of Asia (China and the Gulf Countries in the Middle East). The participants were divided into four separate experimental groups (SBSC-4 without risk, SBSC-4 with risk, SBSC-5 without risk, and SBSC-5 with risk). The data analysis was conducted by using Two-Way ANOVA for group comparisons in a Two-factor factorial design approach, while the moderation effect and the moderated-mediation effect was tested through Hayes Process Macro in SPSS (model 8). The results indicate that there is a significant difference between SBSC-4 and SBSC-5 in terms of their impact on environmental investment decision-making. The difference remains significant in presence of risk indicators. This study also finds that the relationship between the two types of SBSC architecture and environmental investment decision-making is mediated by SBSC knowledge and moderated by risk indicators. This study further examines whether a significant moderated-mediation relationship exists in an integrated model with the two types of SBSC architecture and environmental investment decision-making. The findings of this experimental research suggest that SBSC knowledge and risk indicators influence decision outcomes when the two SBSC configurations are utilized by decision-makers to evaluate environmental investment options.